Changes in perception of illness during cardiac rehabilitation programme among patients with acute coronary syndrome: a longitudinal study - Sukhbeer Kaur Darsin Singh; Fatimah Ahmedy; Abqariyah Yahya Ahmad Noor; Khatijah Lim Abdullah; Imran Zainal Abidin; Anwar Suhaimi (Multidisciplinary Digital Publishing Institute, 2023)
Little is known about the changes in perception of illness among patients with the acute coronary syndrome (ACS) during cardiac rehabilitation programme (CRP). The purpose of this study is to determine changes in perception of illness with ACS patients during CRP to evaluate the association of patients’ characteristics with the perception of illness at the end of Phase II of CRP. A descriptive longitudinal study was conducted among 450 patients who attended 8-weeks of Phase II CRP at 2 public hospitals in Malaysia and perception of illness was assessed using Brief Illness Perception Questionnaire (BIPQ). The assessment was conducted before Phase II (T0), during the 4th session (T1), and at the end of right after the 8th session (T2). One-way repeated measures of ANOVA analysed the changes of perception at T1 and T2 while logistic regression analysis evaluated the association of patients’ characteristics with the perception of illness at T2. Perception of illness changed during and after CRP from T0 to T1, and T1 to T2 (p < 0.001). The patient viewed ACS as an illness that changed from being more acute to a chronic condition as the sessions progressed. Previous history of acute myocardial infarction (OR = 2.380, 95% CI 1.46, 5.49) and angioplasty intervention were both found to be associated with the perception of illness (OR = 3.857, 95% CI 1.55, 9.61). Perception of illness changed during CRP and these changes are associated with patients’ previous history of cardiac events. Phase II can be viewed as the second window of opportunity for healthcare professionals to intervene early in modifying the perception of illness.